Composition and structure of macroinvertebrate communities of lakes in different altitudinal zones of Russian Altai - Vdovina, Olga N.; Yanygina, Liubov V.; Bezmaternykh, Dmitry M. (Acta Biologica Sibirica, 2022)
In 2002-2020, the composition and structure of benthic invertebrate communities from 36 lakes of the Russian Altai located at various (low, mid and high) altitudes were studied. Low-mountain and lowland lakes have a similar zoobenthos structure. With height, the taxonomic structure becomes more complicated, and the dominant taxa of macroinvertebrates change. The peculiar feature of bottom zoocenoses in mid- and high-altitude lakes is high frequency of occurrence and large contribution to the total biomass of crustaceans of the family Gammaridae. We described the trophic structure of zoobenthos and identified five main trophic groups. In terms of species number, the collector-detritus feeder and predator groups dominated in the trophic structure of all lakes. By biomass, the growing proportion of filter feeders and shredders was observed with increasing height.